NREM Sleep Instability in Pediatric Migraine Without Aura - Roccella, Michele; Marotta, Rosa; Operto, Francesca Felicia; Smirni, Daniela; Precenzano, Francesco; Bitetti, Ilaria; Messina, Giovanni; Sessa, Francesco; Di Mizio, Giulio; Loreto, Carla; Salerno, Monica; Russo, Vincenzo; et al. (Frontiers in Neurology, 2019)
Children with migraine headaches appear to have a range of sleep disturbances. The aim of the present study was to assess the NREM sleep instability in a population of school-aged individuals affected by migraine without aura (MoA). 33 children with MoA (20 males, 13 females, mean age 10.45±2.06 years) underwent to overnight PSG recordings and Cyclic Alternating Pattern (CAP) analyses accordingly with international criteria. MoA group showed a reduction in sleep duration parameters (TIB, SPT, TST; p≤0.001 for all) and in arousal index during REM sleep and an increase in awakenings per hour (AWK/h) (p=0.008). In particular, MoA children showed a reduced CAP rate% (p≤0.001), CAP rate% in S1 (p≤0.001) and CAP rate% in SWS (p=0.004) vs. control subjects (C). Moreover, A phases distribution were characterized by a reduction in slow wave components (total number CAP A1%, CAP A1 index) (p≤0.001) and an increase of fast components (total number of CAP A2% and CAP A3%) representation in MoA vs. C. Moreover, MoA children showed an increased A1 and A2 mean duration (p≤0.001). Our findings show a poor sleep quality and lower NREM lower sleep instability associated with MoA in children.